Estudio de la progresión en la delimitación de las "ideas" del alumno sobre fuerza - Jiménez Gómez, Emma; Solano Martínez, Isabel; Marín Martínez, Nicolás (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
The aim of this paper is to analyse if there has been any progress in the results that different papers about learners’ «ideas» have shown in Dynamics. To that end, a wide sample of papers about «pupils' knowledge» concerning the concept of force has been chosen and a set of categories has been establihed in order to set up the criteria that allow us to compare the information presented in those papers.